2019
DOI: 10.3344/kjp.2019.32.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal analgesia with multiple intermittent doses of erector spinae plane block through a catheter after total mastectomy: a retrospective observational study

Abstract: Background Although case reports have suggested that the erector spinae plane block (ESPB) may help analgesia for patients after breast surgery, no study to date has assessed its effectiveness. This retrospective observational study analyzed the analgesic effects of the ESPB after total mastectomy. Methods Forty-eight patients were divided into an ESPB group (n = 20) and a control group (n = 28). Twenty patients in the control group were selected by their propensity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Therefore, to maximize the effect of RLB and to effectively control postoperative pain, we suggest that this block should be performed at the end of the surgery. Considering a recent study on the erector spinae plane block, which is similar to the RLB [29], the continuous infusion method in the RLB could be a good option for adequate postoperative analgesia following breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to maximize the effect of RLB and to effectively control postoperative pain, we suggest that this block should be performed at the end of the surgery. Considering a recent study on the erector spinae plane block, which is similar to the RLB [29], the continuous infusion method in the RLB could be a good option for adequate postoperative analgesia following breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is conflicting opinion as to whether this block may be effective in managing postoperative pain. Several clinical studies have shown that the ESPB may be effective in postoperative pain control for various types of thoraco-abdominal surgery [ 7 - 11 ], while, there have been some contrary results suggesting that the ESPB has a limited effect on postoperative pain control [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-mastectomy analgesia consists of many regional techniques. [1] Paravertebral block (PVB) is the most effective studied technique, but due to its anatomic proximity to pleura and central neuroaxial system, it is a challenging one. [2] Erector spinae plane block (ESPB) has been used successfully for post-operative analgesia in breast surgeries.…”
Section: Introductionmentioning
confidence: 99%